Safety and Efficacy of Lofexidine for Medically Managed Opioid Withdrawal: A Randomized Controlled Clinical Trial. Issue 3 (May 2019) - Fishman, Marc; Tirado, Carlos; Alam, Danesh; Gullo, Kristen; Clinch, Thomas; Gorodetzky, Charles W.
Abstract : Objectives: To investigate the safety and efficacy of lofexidine for treating opioid withdrawal syndrome (OWS) and facilitating completion of opioid withdrawal. Methods: A multicenter, double-blind, placebo-controlled study was conducted at 18 US centers from June 2013 to December 2014. Participants (n = 603) aged ≥18 years, dependent on short-acting opioids, and seeking withdrawal treatment, randomized 3:3:2 to receive lofexidine 2.88 mg/d (n = 222), lofexidine 2.16 mg/d (n = 230), or placebo (n = 151) for 7 days. Primary outcome was the Short Opiate Withdrawal Scale of Gossop (SOWS-Gossop) scores rating withdrawal symptoms over days 1 to 7. Results: Participants were of mean age, 35 years; 71% male. Pairwise differences in overall SOWS-Gossop log-transformed least squares means were statistically significant for lofexidine 2.16 mg (difference, −0.21; 95% CI, −0.37 to −0.04; P = 0.02) and 2.88 mg (−0.26; 95% CI, −0.44 to −0.09; P = 0.003) compared with placebo. Fewer than half of participants in both groups completed the study. Completion rates for lofexidine 2.16 mg (41.5%; odds ratio [OR], 1.85; P = 0.007) and 2.88 mg (39.6%; OR, 1.71; P = 0.02) were significantly better compared with placebo (27.8%). Overall adverse event (AE) rates were similar across groups. Common AEs for lofexidine included orthostatic hypotension, hypotension, and bradycardia, but resulted in few study discontinuations. Conclusions: Lofexidine 2.16 mg and 2.88 mg significantly reduced symptoms of OWS versus placebo, and increased absolute rates of completing the 7-day study by 14% and 12%, respectively (a relative increase of 85% and 71%). Data suggest that lofexidine is a generally safe and effective nonopioid treatment for opioid withdrawal. Lofexidine could serve as a withdrawal treatment option when a nonopioid agent is preferred or required, when agonist-assisted withdrawal is unavailable, when agonist discontinuation caused OWS, and during induction into maintenance treatment with opioid agonists or antagonists. Trial Registration: ClinicalTrials.gov identifier: NCT01863186. Abstract : Supplemental Digital Content is available in the text